2016
DOI: 10.5812/ircmj.26613
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Burn Wound Closure in Mice with a New Formula Based on Traditional Medicine

Abstract: BackgroundA combination of the oils of sesame, hemp, wild pistachio, and walnut has been used for treatment of skin disorders, including wound burns, in some parts of Kerman, Iran. Evaluation of this remedy in the form of a pharmaceutical formulation in animal models can pave the way for its future application in wound burn healing in humans.ObjectivesThis experimental study investigated the healing potential of a new formula (NF) based on folk medicine from Iran for the treatment of third degree burns in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…This new formula increased wound contraction and accelerated epithelialization. 21 Hamidi et al . showed that P. atlantica oil as gels ameliorated epithelialization which is as a marker of wound contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new formula increased wound contraction and accelerated epithelialization. 21 Hamidi et al . showed that P. atlantica oil as gels ameliorated epithelialization which is as a marker of wound contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The wound contractions was reported as percent and were calculates by following formula: 21 %wound contraction=(wound area [day 1]-wound area [day 14]/wound area [day 1]×100…”
Section: Methodsmentioning
confidence: 99%
“…Wound healing has different stages including inflammation, proliferation, and reconstruction, each consisting of several other steps, some of which overlaps with each other and thus are not easily separable (24,25). Therefore, the qualitative and quantitative improvement of each of these stages can accelerate wound healing and reduce its complications.…”
Section: Discussionmentioning
confidence: 99%
“…This model resembles the clinical situation and provides an opportunity to examine or develop new strategies such as new antibiotics and immune therapy for handling burn wound. Moreover, a 25% third-degree burn injury was demonstrated by exposure to boiling water for examining the efficacy of new formula-based traditional medicine [34]. Although burn mouse model has its specific advantages, evidently this model fails to completely mimic the wound healing process of humans.…”
Section: Mousementioning
confidence: 99%